No excess long‐term mortality in stage I‐IIA Hodgkin lymphoma patients treated with ABVD and limited field radiotherapy. (14th October 2019) - Lagerlöf, Ingemar; Holte, Harald; Glimelius, Ingrid; Björkholm, Magnus; Enblad, Gunilla; Erlanson, Martin; Fluge, Øystein; Fohlin, Helena; Fosså, Alexander; Goldkuhl, Christina; Gustavsson, Anita; Johansson, Ann‐Sofie; et al.
Summary: When treating limited stage classical Hodgkin lymphoma (cHL), balancing treatment efficacy and toxicity is important. Toxicities after extended‐field radiotherapy are well documented. Investigators have aimed at reducing toxicity without compromising efficacy, mainly by using combined modality treatment (CMT), i.e. chemotherapy and limited‐field radiotherapy. In some clinical trials, radiotherapy has been omitted. We evaluated 364 patients with stage I‐IIA cHL treated between 1999 and 2005. Patients were treated with two or four cycles of doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD) according to presence of risk factors, followed by 30 Gy limited‐field (reduced compared to involved‐field) radiotherapy. After a median follow‐up of 16 years for survival, freedom from progression at five and ten years was 93% and overall survival at 5 and 10 years was 98% and 96%, respectively. Only two relapses, out of 27, occurred after more than 5 years. There was no excess mortality compared to the general population. Of the analysed subgroups, only patients with progression within five years showed significant excess mortality. The absence of excess mortality questions the concept of omitting radiotherapy after short‐term chemotherapy, a strategy that has been associated with an elevated risk of relapse but not yet with a proven reduced long‐term excess mortality.